2005
DOI: 10.1097/01.smj.0000154775.16761.a9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation: Nutritional, Botanical, and Mind-body Influences

Abstract: Chronic inflammation is becoming an important risk factor to identify in regard to inhibiting disease onset and its progression. Nutritional science attempted to improve health by manipulating fats so that we could consume "healthy" nonsaturated fats while simultaneously allowing foods to have a longer shelf-life. However, despite our good intentions, trans-fats and partially hydrogenated oils have been found to promote inflammation and adversely affect health. This article reviews how essential fatty acids, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In response to inflammation, the body activates cells in the immune response, which increase the production of pro-inflammatory mediators including nitrogen and prostaglandin. Earlier studies demonstrated that excessive production of nitrogen and prostaglandin takes part in inflammatory diseases, including rheumatoid arthritis, asthma and cancer [ 132 , 133 ]. Their high levels are produced by inductive enzymes such as inductive nitric oxide synthase and cyclooxygenase-2 [ 134 ].…”
Section: Pharmacological Activity Health-promoting Propertiesmentioning
confidence: 99%
“…In response to inflammation, the body activates cells in the immune response, which increase the production of pro-inflammatory mediators including nitrogen and prostaglandin. Earlier studies demonstrated that excessive production of nitrogen and prostaglandin takes part in inflammatory diseases, including rheumatoid arthritis, asthma and cancer [ 132 , 133 ]. Their high levels are produced by inductive enzymes such as inductive nitric oxide synthase and cyclooxygenase-2 [ 134 ].…”
Section: Pharmacological Activity Health-promoting Propertiesmentioning
confidence: 99%
“…They inhibit IL‐2, TNF‐α, and IL‐8, which are proinflammatory cytokines; they also inhibit leukotriene and prostaglandin synthesis 83 – 87 . Additionally, garlic, cayenne, and oregano have anti‐inflammatory properties and should be added to food while preparing meals 88 …”
Section: Additional Componentsmentioning
confidence: 99%
“…Digestive health remains a central tenant of functional medicine [ 11 ], Ayurveda [ 12 ], naturopathic medicine [ 13 ] and traditional Chinese Medicine [ 14 ]. Finally, the holistic nature of integrative care with a mind-body emphasis often results in treatment plans incorporating psychological and somatic therapies [ 15 , 16 ].…”
Section: Holism and Systems Healthmentioning
confidence: 99%